2013
DOI: 10.1371/journal.pone.0066306
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Proliferation Require Down-Regulation of Host Nox4 Expression via Activation of PI3 Kinase/Akt Signaling Pathway

Abstract: Toxoplasma gondii results in ocular toxoplasmosis characterized by chorioretinitis with inflammation and necrosis of the neuroretina, pigment epithelium, and choroid. After invasion, T. gondii replicates in host cells before cell lysis, which releases the parasites to invade neighboring cells to repeat the life cycle and establish a chronic retinal infection. The mechanism by which T. gondii avoids innate immune defense, however, is unknown. Therefore, we determined whether PI3K/Akt signaling pathway activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 47 publications
(58 reference statements)
4
46
0
5
Order By: Relevance
“…Innate immune responses triggered by TLR signaling are mediated through the generation of intracellular ROS, which are now being recognized as important secondary messengers (21,22,24 activation of the PI3K/AKT signaling pathway in human retinal epithelium cells (19). Additionally, a recent study showed that T. gondii induced the NOX1-dependent production of excessive ROS, which contributed to mitochondrial structural damage and mitochondrial dysfunction in placentas, as well as the cleavage of caspase-9 and caspase-3, which resulted in the apoptosis of trophoblasts (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Innate immune responses triggered by TLR signaling are mediated through the generation of intracellular ROS, which are now being recognized as important secondary messengers (21,22,24 activation of the PI3K/AKT signaling pathway in human retinal epithelium cells (19). Additionally, a recent study showed that T. gondii induced the NOX1-dependent production of excessive ROS, which contributed to mitochondrial structural damage and mitochondrial dysfunction in placentas, as well as the cleavage of caspase-9 and caspase-3, which resulted in the apoptosis of trophoblasts (35).…”
Section: Discussionmentioning
confidence: 99%
“…Although intracellular ROS as a secondary messenger can regulate infection signaling against T. gondii (19,26), ROS formation in response to toxoplasma antigens is poorly characterized. We first determined whether stimulation with rGRA7 leads to ROS generation in murine BMDMs.…”
Section: T Gondii Gra7 Protein Leads To Mapk and Nf-b Activation Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is still unknown whether there is a connection between host cell and tachyzoites in the modulation of the parasite replication process. The treatment of host cells with phosphatidylinositide 3-kinases (PI3K kinases) inhibitors such as LY294002 and wortmannin has been shown to reduce tachyzoite replication (Zhou et al 2013). TgHsp90 PPI analysis has shown several putative kinases and phosphatases that could be involved in cell signalling (Table S1).…”
Section: The Cell Cyclementioning
confidence: 99%